Protein restriction during pregnancy impairs intra-islet GLP-1 and the expansion of β-cell mass. (1st December 2020) - Pereira de Arruda, Edson Henrique; Vieira da Silva, Gleicielly Leite; da Rosa-Santos, Chaiane Aline; Arantes, Vanessa Cristina; de Barros Reis, Marise Auxiliadora; Colodel, Edson Moleta; Gaspar de Moura, Egberto; Lisboa, Patrícia Cristina; Carneiro, Everardo Magalhães; Damazo, Amílcar Sabino; Latorraca, Márcia Queiroz
Abstract: We evaluated whether protein restriction during pregnancy alters the morphometry of pancreatic islets, the intra-islet glucagon-like peptide-1 (GLP-1) production, and the anti-apoptotic signalling pathway modulated by GLP-1. Control non-pregnant (CNP) and control pregnant (CP) rats were fed a 17% protein diet, and low-protein non-pregnant (LPNP) and low-protein pregnant (LPP) groups were fed a 6% protein diet. The masses of islets and β-cells were similar in the LPNP group and the CNP group but were higher in the CP group than in the CNP group and were equal in the LPP group and the LPNP group. Both variables were lower in the LPP group than in the CP group. Prohormone convertase 2 and GLP-1 fluorescence in α-cells was lower in the low-protein groups than in the control groups. The least PC2/glucagon colocalization was observed in the LPP group, and the most was observed in the CP group. There was less prohormone convertase 1/3/glucagon colocalization in the LPP group than in the CP group. GLP-1/glucagon colocalization was similar in the LPP, CP and CNP groups, which showed less GLP-1/glucagon colocalization than the LPNP group. The mRNA Pka, Creb and Pdx-1 contents were higher in islets from pregnant rats than in islets from non-pregnant rats. Protein restriction during pregnancy impaired the mass of β-cells and the intra-islet GLP-1 production but did not interfere with the transcription of genes of the anti-apoptotic signalling pathway modulated by GLP-1. Highlights: Protein restriction during pregnancy did impair the expansion of α- and β-cell mass. Protein restriction during pregnancy impaired intra-islet GLP-1 production and content. PC2/glucagon colocalization was reduced in pregnant protein-restricted rats. Low GLP-1 concentrations did not compromise β-cell proliferative capacity.